Optical Methods of Imaging In-plane and Normal Load Distributions Between Contacting Bodies - Tompkins, Christopher G (2023)
The work presented here details the creation of two novel force sensors: one which gives a direct optical measure of contact forces using Frustrated Total Internal Reflection, and another which measures the in-plane traction forces between contacting bodies using a matrix of dye-doped dots suspended in an elastomer film. The application of these devices shows how unique information of the contact mechanics between two bodies can be gathered. The contact device is used to study lower-body biomechanics during simple training exercises. The traction device is used for a more fundamental study of the shape dependence of friction in elastic media. This has resulted in a correction factor to the force distributions which may be used to increase the accuracy of simulations of this friction regime. It has also been determined that the shape dependence of friction is likely caused by compressive strain at the interface, and the mechanics of this investigated.